Understanding the stability of low- and high-acid, high-protein dairy-based beverages - Zaitoun, Baheeja Jameel (Kansas State University, 2024)
High-protein dairy beverages have become increasingly popular among health-conscious and athletic individuals owing to their nutritional advantages and convenience. These beverages can be categorized into two types: low-pH and high-pH drinks. In high-pH beverage formulations, milk protein concentrates (MPCs) are used as the primary protein source, while whey protein concentrates (WPCs) are applied in low-pH drink formulations. The nature of the protein source ingredient used in manufacturing those beverages impacts the formulation, processing conditions, and challenges faced during processing and storage. For instance, MPC-based drinks contain emulsifying salts such as sodium hexametaphosphate (SHMP) to improve those beverages' heat and physiochemical properties. In addition, heat treatment such as UHT (138°C for at least 2 s) or retort sterilization (115–120°C for 5–15 min) is required to achieve the product’s safety and shelf stability. The key challenge faced by the industry for such products is the difficulty of determining product stability in the early stages of storage, as product stability issues tend to manifest as physical changes later in the product's shelf life as an indication of sedimentation or age gelation. Hence, there is a pressing need for a predictive method capable of identifying changes in the stability of high-pH drinks during their early stages. In this research, the influence of using different phosphate chain lengths of SHMP on the heat stability and physiochemical properties of high protein dispersions was investigated in Chapter 3. SHMP with different chain lengths were added to the high-protein dispersions; then, samples were tested for apparent viscosity, heat coagulation time (HCT), mean particle size and zeta potential, FAST index, color, and turbidity. Therefore, this study suggests that the short phosphate chain SHMP might be the most suitable emulsifying salt in UHT and retort sterilized high protein beverages. Chapter 4 focuses on validating Electrical Resistance Tomography (ERT) as an innovative method for detecting early-stage destabilization in high-protein drinks. ERT detection is based on measuring the changes in the electrical conductivity, which are then translated into tomograms. These tomograms serve as images reconstructed using the back-linear projection technique via ERT software, effectively predicting destabilization caused by sedimentation or age gelation. On the other hand, using acidulants is crucial in processing WPC-based drinks to have clear beverages that meet the consumer's acceptability and expectations. With advanced filtration technologies, whey proteins are made of skim milk through microfiltration processes called milk whey protein isolate (mWPI). As mWPI is an innovative ingredient that can be applied in the formulation of low-pH drinks, developing stability diagrams that can be used as a tool for the industry to identify and predict the turbidity and stability of acidic beverages is needed. Therefore, chapter 5 investigated the development of stability diagrams of acidic beverages using the mWPI as a source of protein to help the industry manufacture a more desirable and shelf-stable acidic whey drink with the possibility of producing a higher protein content.
Keywords: High protein dairy-based beverages